Pregnancy Associated Osteoporosis - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2013)
Osteoporosis is a systemic skeletal disease characterized by low bone mass and microarchitectural deterioration of bone tissue. While osteoporosis is seen very often, osteoporosis in pregnancy is a rare clinical problem with unknown etiology and pathophysiology. Whether pregnancy is accidental or is a direct cause for osteoporosis are the questions that remain unanswered. The normal pregnancy and lactation-induced changes in bone and mineral metabolism allow adequate delivery of calcium to the fetus, mostly in the last trimester of pregnancy. Therefore, pregnancy and lactation may have significant impact on bone loss and this may result in pregnancy-induced osteoporosis and the related fractures. The symptoms occur often during the first pregnancy and usually does not recur. Secondary causes of osteoporosis that may cause back pain and fractures during pregnancy should also be taken into consideration. Recently, no guidelines exist about the therapy of pregnancy associated osteoporosis, this means each case must be evaluated on an individual basis in order to decide on a treatment plan.
Keywords: Pregnancy; lactation; osteoporosis; TERM-FOLLOW-UP; TRANSIENT OSTEOPOROSIS; BONE-DENSITY; VERTEBRAL FRACTURES; LACTATION; CALCIUM; VITAMIN-K-2; WOMEN; HIP; BISPHOSPHONATE